The Influence of Environmental Awareness, Eco-Label, Eco-Brand, and Environmental Advertisement on Purchase Intention of Environmentally Friendly Products - Owen De Pinto Simanjuntak; Esther Praja Anggriany Panggabean; Khairunnisa Abd Samad (Bina Nusantara University, 2026)
The research investigated the influence of environmental awareness, eco-brand, eco-label, and green advertising on consumers’ purchase intention toward eco-friendly products, with environmental knowledge examined as a moderating variable. Data were collected from 205 environmentally conscious consumers through an online survey designed to capture their perceptions and purchasing behaviors. The measurement and structural models were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS), enabling a robust evaluation of the relationships among constructs. The results indicate that environmental awareness, eco-brand, eco-label, and green advertising each exert a significant positive influence on consumers’ purchase intention. Notably, environmental knowledge plays a moderating role, strengthening the relationship between green advertising and purchase intention. The findings suggest that consumers with higher environmental knowledge are more responsive to green marketing efforts and more likely to engage in environmentally responsible consumption. These findings underscore the importance of consumer knowledge and perception in fostering sustainable purchasing behavior and contribute to the growing literature on green marketing. The research offers practical implications for companies seeking to enhance their green marketing strategies and for policymakers aiming to encourage environmentally responsible consumer behavior through awareness programs and sustainable product labeling. Recommendations for future research include investigating other potential moderating or mediating variables, expanding the scope to include different demographic and cultural contexts, and conducting longitudinal studies to examine how green consumer behavior evolves over time. Highlighting the moderating effect of environmental knowledge can help to build a more comprehensive understanding of sustainable consumption dynamics across diverse markets.